2019
DOI: 10.3390/w12010018
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Connectivity in Two Ancient Lakes: Impact Upon Planktonic Cyanobacteria and Water Quality

Abstract: The ancient lakes Mikri Prespa and Megali Prespa are located in SE Europe at the transnational triangle and are globally recognized for their ecological significance. They host hundreds of flora and fauna species, and numerous types of habitat of conservational interest. They also provide a variety of ecosystem services. Over the last few decades, the two lakes have been interconnected through a surface water channel. In an attempt to explore whether such a management practice might alter the ecological proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 42 publications
(61 reference statements)
1
13
0
Order By: Relevance
“…In study period, we found the phytoplankton community was mainly contributed by Cyanophyta and Bacillariophyta. The phytoplankton dynamics in study area are similar to those of small European and African interconnected habits such as Lake Naivasha 25 , Lake Mikri Prespa 12 , and Mississippi River 26 . Environmental variables such as flow rate, velocity, light and nutrient availability are vital characteristics that www.nature.com/scientificreports/ directly affect the diversity and dispersal of phytoplankton in rivers and wetlands 2,21,27 .…”
Section: Impacts Of Hydrological Connectivity On Phytoplankton Communsupporting
confidence: 56%
See 2 more Smart Citations
“…In study period, we found the phytoplankton community was mainly contributed by Cyanophyta and Bacillariophyta. The phytoplankton dynamics in study area are similar to those of small European and African interconnected habits such as Lake Naivasha 25 , Lake Mikri Prespa 12 , and Mississippi River 26 . Environmental variables such as flow rate, velocity, light and nutrient availability are vital characteristics that www.nature.com/scientificreports/ directly affect the diversity and dispersal of phytoplankton in rivers and wetlands 2,21,27 .…”
Section: Impacts Of Hydrological Connectivity On Phytoplankton Communsupporting
confidence: 56%
“…Be contrary to diatoms, unexpected, there was no significant variation of abundance of Cyanophyta in the interconnected habits during differ hydrological period. Katsiapi et al (2020) noted that the motile species of Cyanophyta and Euglenophyta were dominated in connectivity lakes 12 . Cyanophyta (Pseudanabaena spp.)…”
Section: Impacts Of Hydrological Connectivity On Phytoplankton Communmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of hydrogeomorphological features in shaping cyanobacterial communities as subcommunities of the phytoplankton community was showcased in two papers of the current Special Issue. Yao et al [19] investigated a 2-year succession of cyanobacteria and eukaryotic phytoplankton functional groups in a reservoir, while Katsiapi et al [14] used a system of two recently interconnected ancient lakes to show that this recent mode of water translocation between the two lakes increased the occurrence of potentially toxic and bloom-forming cyanobacteria. Another study with a dataset covering a whole decade between 2004 and 2014 reported that cyanobacteria constituted up to 60% of the primary producer biovolume, with increased dominance after 2010 [18].…”
Section: Contributionsmentioning
confidence: 99%
“…In this direction, a deeper understanding of the mechanisms that determine cyanobacterial bloom structure and toxin production become a target for managing practices [5,6]. This Special Issue, entitled "Advancing Knowledge on Cyanobacterial Blooms in Freshwaters", includes 11 research papers [9][10][11][12][13][14][15][16][17][18][19] and aims to bring together the recent research of multiand interdisciplinary approaches from the field to the laboratory and back again, driven by working hypotheses based on any aspect from ecological theory to applied research on mitigating cyanobacterial blooms.…”
Section: Introductionmentioning
confidence: 99%